2002
DOI: 10.1016/s1074-5521(02)00238-7
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Affinity Fingerprinting

Abstract: Classifying proteins into functionally distinct families based only on primary sequence information remains a difficult task. We describe here a method to generate a large data set of small molecule affinity fingerprints for a group of closely related enzymes, the papain family of cysteine proteases. Binding data was generated for a library of inhibitors based on the ability of each compound to block active-site labeling of the target proteases by a covalent activity based probe (ABP). Clustering algorithms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
82
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 31 publications
0
82
0
Order By: Relevance
“…To determine the protease component of this activity, affinity labeling was performed with the cysteine protease activity probe known as DCG-04 ( Fig. 1a) (14,15). Affinity labeling at various stages in the purification demonstrated enrichment of a DCG-04-labeled 27-kDa protease band (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the protease component of this activity, affinity labeling was performed with the cysteine protease activity probe known as DCG-04 ( Fig. 1a) (14,15). Affinity labeling at various stages in the purification demonstrated enrichment of a DCG-04-labeled 27-kDa protease band (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study the protease responsible for PE-cleaving activity in chromaffin granules was identified by using an activity-based probe for cysteine proteases (14,15) combined with mass spectrometry (MS) for peptide sequencing. Results identified secretory vesicle cathepsin L as the enzyme responsible for the previously described PTP cysteine protease activity involved in enkephalin and neuropeptide production (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Active Site Labeling of Cysteine Proteinases-Active site labeling experiments of cysteine proteinases were performed as previously described (19,30) with some modifications. Briefly, lysosomal fractions from MDMs were incubated with or without Mu-Leu-Hph-VS-Ph (1 nM or 1 M), a highly potent irreversible cathepsin S inhibitor (31), with Mu-Np2-Hph-VS-2Np (10 nM), a potent general cathepsin but very weak cathepsin K inhibitor (32, 33) (both inhibitors were kindly provided by Celera Corp., South San Francisco, CA), or with CA074 (100 nM; Calbiochem, La Jolla, CA), a selective cathepsin B inhibitor, at 37°C for 1 h prior to incubation with a biotin and tyrosine residue containing E-64 derivative (DCG-04) (50 M) for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Labeling of this protein could be blocked by pretreatment with the pan-cathepsin inhibitor, JPM-565, as well as the cathepsin B specific inhibitor CA074 (Supplemental Fig 1) suggesting it was in fact cathepsin B. This was a surprising result since profiling studies performed on the cysteine cathepsins had previously demonstrated that these proteases do not tolerate negatively charged amino acid residues in the P2 position in either substrates or epoxide-based inhibitors [12,14,16].…”
mentioning
confidence: 89%
“…For each sub-library either the P2, P3 or P4 position was held constant as a single amino acid while the remaining positions were coupled with an equal mixture of 19 amino acids (all 20 natural amino acids minus cysteine and methionine to avoid dimerization and oxidation problems and plus norleucine as a structural analog for methionine) as has been reported previously [12]. Scanning of the natural amino acid sequences through each of the P2-P4 positions provided a specificity fingerprint for legumain that could then be used to select optimal residues for the design of legumain-directed probes.…”
mentioning
confidence: 99%